Estudo das Técnicas de Bioengenharia, Motomecanização e a Implantação de Parque Linear na Bacia do Córrego do Limoeiro | A Study of Bioengineering Techniques, Mechanization and Implementation at the Basin of the Limoeiro Stream - Gonçalves, Diogo Laercio (PEGADA - A Revista da Geografia do Trabalho, 2014)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–> Introduction: The main focus of this study is the application of knowledge concerning technology and techniques of environmental recovery in Permanent Preservation Areas (APP) at the basin of the Limoeiro stream, comprising the Balneário da Amizade in the municipalities of Álvares Machado and Presidente Prudente, in the State of São Paulo, particularly in the Residencial Maré Mansa and Parque Imperial neighbour hoods, taking account of the importance of APPs in the life of the urban population. Among the main objectives of this research, is a study of the techniques and technology of soil bioengineering in the recovery of the banks of the stream along with mechanization techniques used by the São Paulo Agricultural Development Company (CODASP) at its regional headquarters in Presidente Prudente. It is hoped to elaborate on plans for environmental restoration in the basin area of the Limoeiro stream with research for the betterment of the population, as well as outlining a proposal for a linear park with the objective of incorporating an APP in the district, looking towards a better integration between society and nature. Methodology and Development: The methodological procedures covered in this research include a literary review of such topics as bioengineering, APPs, and environmental legislation, as well as field work with CODASP to identify mechanization techniques used to counter erosion. ALOS Satellite images, available at UNESP, are being used to determine the character of the stream basin, plus the cartographic databases of IGC, CPRM and IBGE, part of the GADIS research group, using ArcGIS and SPRING software. We propose to forward the results of this survey to the relevant bodies such as the municipalities of both cities and the River Basin Committee of Pontal do Paranapanema in the hope that these organs will take action to improve the lives of residents in the basin area. Final thoughts: The results reached so far in the survey point to a need for joint action by the relevant bodies to improve the area, particularly the urban parts. It is hoped that environmental restoration techniques and the proposed linear park to improve the leisure facilities of the local population will bring together the interests of both parties, guaranteeing sustainability and greater environmental benefit in the region of the basin of the Limoeiro stream, bearing in mind its importance in supplying water to the cities. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>